Youth Empowerment Solutions: Evaluation of an After-School Program to Engage Middle School Students in Community Change. (February 2018) - Zimmerman, Marc A.; Eisman, Andria B.; Reischl, Thomas M.; Morrel-Samuels, Susan; Stoddard, Sarah; Miller, Alison L.; Hutchison, Pete; Franzen, Susan; Rupp, Laney
We report on an effectiveness evaluation of the Youth Empowerment Solutions (YES) program. YES applies empowerment theory to an after-school program for middle school students. YES is an active learning curriculum designed to help youth gain confidence in themselves, think critically about their community, and work with adults to create positive community change. We employed a modified randomized control group design to test the hypothesis that the curriculum would enhance youth empowerment, increase positive developmental outcomes, and decrease problem behaviors. Our sample included 367 youth from 13 urban and suburban middle schools. Controlling for demographic characteristics and pretest outcome measures, we found that youth who received more components of the curriculum reported more psychological empowerment and prosocial outcomes and less antisocial outcomes than youth who received fewer of the intervention components. The results support both empowerment theory and program effectiveness.